2011
DOI: 10.1108/02683941111164490
|View full text |Cite
|
Sign up to set email alerts
|

Influence and promotability: the importance of female political skill

Abstract: Purpose -The current paper seeks to bring the political perspective to gender differences in promotion decisions, a phenomenon with great longevity in research and practice. Specifically, the degree to which gender role-congruent and counterstereotypical influence behavior is related to liking as moderated by political skill. Design/methodology/approach -Using a sample of n ¼ 136, these hypotheses were tested in retail organizations in the Northeast and Southwest. Findings -Political skill significantly modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 67 publications
(98 reference statements)
1
27
0
Order By: Relevance
“…The intersection of EI and employee satisfaction was also found among Eastern European employees (Zadel, 2008). Furthermore, men who employed more aggressive upward influence behavior were rated to be higher performers than those who used weaker tactics such as friendliness (Shaughnessy et al, 2011). Therefore, upward influence behavior and EI as antecedents to employee satisfaction and performance may attract attention of researchers.…”
mentioning
confidence: 85%
“…The intersection of EI and employee satisfaction was also found among Eastern European employees (Zadel, 2008). Furthermore, men who employed more aggressive upward influence behavior were rated to be higher performers than those who used weaker tactics such as friendliness (Shaughnessy et al, 2011). Therefore, upward influence behavior and EI as antecedents to employee satisfaction and performance may attract attention of researchers.…”
mentioning
confidence: 85%
“…While political skill is the ability to execute political behaviours competently, political will represents an individual's motivation to engage in such behaviours (Doldor et al 2013). Some studies have found that even politically skilled individuals cannot achieve desirable outcomes unless they engage in political behaviour (Shaughnessy et al 2011;Shi et al 2013). Some studies have found that even politically skilled individuals cannot achieve desirable outcomes unless they engage in political behaviour (Shaughnessy et al 2011;Shi et al 2013).…”
Section: Moderators Of the Effects Of Political Skillmentioning
confidence: 99%
“…In a recent study, Carlson and his colleagues () found that deceptive IM is negatively related to promotability ratings. On the contrary, Shaughnessy et al () did not find a positive association between IM tactics (i.e., ingratiation and assertiveness) and promotability ratings. However, they observed that use of ingratiation is positively related to liking when women deploy political skills.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 89%
“…For example, Carlson and his colleagues () used a six‐item scale adapted from Kumar and Beyerlein's () Measure of Ingratiatory Behaviors in Organizational Settings (MIBOS) and Wayne and Ferris’ scale () of a subordinate's deceptive IM strategies. Shaughnessy, Treadway, Breland, Williams, and Brouer () used a three‐item scale adapted from Schriesheim and Hinkin (). However, Bolino and Turnley () raised serious concerns about the validity and reliability of these scales.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%